2012
DOI: 10.1097/sap.0b013e31821d0531
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Recipient Veins in Microsurgical Flap Reconstructions of the Lower Extremities

Abstract: It is difficult to cure severe open fractures of the lower extremities due to the frequent occurrence of severe damage to soft tissues or blood vessels, as well as bone defects, and concomitant infection, such as osteomyelitis. If appropriate treatment is not performed, long-term complications, such as nonunion of the bone, intractable ulcers, or other disorders, may arise. Between 1993 and 2010, we reviewed the records of 27 patients, and 28 limbs were treated. A total of 31 free-tissue transfers were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…A total of 11 articles were eligible for inclusion, including three case reports (810), three case series (1113), and five retrospective studies (Fig. 1) (1416).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 11 articles were eligible for inclusion, including three case reports (810), three case series (1113), and five retrospective studies (Fig. 1) (1416).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the MDB Quality Assessment Tool (5,17), three papers were of good quality (14,15,18) and two were of fair quality (16,19). None of the studies reported the reliability or validity of the paper, nor did they report the sample size or power calculation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 In summary, we would like to state that the evidence in the article suggesting that acute free flap reconstruction within the zone of trauma is safe might not be conclusive, and that more clinical experience including larger number of patients and different kind of flaps may help to bring more valuable knowledge in this topic.…”
Section: Dear Sirmentioning
confidence: 94%